PERENDAMAN BIJI CENDANA (Santalum album Linn.) DENGAN BERBAGAI KONSENTRASI AIR KELAPA MUDA UNTUK MENINGKATKAN KUALITAS PERKECAMBAHAN - Christian Edwin Haky; Mamie M. E. Pelondo'u; Nixon Rammang (Wana Lestari, 2020)
Sandalwood (Santalum album Linn.) is an endemic species of Indonesia and has natural distribution in East Nusa Tenggara Province. It is the best Sandalwood in the world. The population of Sandalwood (Santalum album Linn.) in East Nusa Tenggara Province has recently experienced a pretty drastic degradation. This research aims to know the effect soaking Sandalwood (Santalum albumLinn.) seeds with various concentrations of young coconut water has on the seed germination. This research was conducted at the Permanent Forest Nursery Center, Watershed Management Agency, Benain – Noelmina, Kupang City. This Research lasted for three months, from December 2018 till March 2019. This research was conducted with completely Randomized Design with five treatments of young coconut water concentration, each treatment was repeated three times and there were 15 experimental units. Each experiment required 100 seeds, so the total of all treatments and replications required 1,500 Sandalwood seeds. The result of research indicated that treatment with various concentrations of young coconut water has a significant effect on germination and germination index. The best young coconut water concentration that is recommended is 75% concentration (250 ml aquades + 750 ml young coconut water)for the best result in Sandalwood (Santalum album Linn.) germination.